2017
DOI: 10.1111/jipb.12505
|View full text |Cite
|
Sign up to set email alerts
|

Development and utilization of a new chemically‐induced soybean library with a high mutation density

Abstract: Mutagenized populations have provided important materials for introducing variation and identifying gene function in plants. In this study, an ethyl methanesulfonate (EMS)‐induced soybean (Glycine max) population, consisting of 21,600 independent M2 lines, was developed. Over 1,000 M4 (5) families, with diverse abnormal phenotypes for seed composition, seed shape, plant morphology and maturity that are stably expressed across different environments and generations were identified. Phenotypic analysis of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 69 publications
(85 reference statements)
3
32
0
Order By: Relevance
“…One soybean mutant (1 % EMS and 8 hours incubation) was not included in the clustering analysis because the seeds cannot grow caused by the toxicity of EMS. This condition was in accordance with the result of Li et al (2017) that a high concentration of EMS showed reduced emergence and physiological damage, including inhibition of the main stem even failed to grow. The dendrogram of genetic relationship resulted in 2 major groups (Figure 3).…”
Section: Cluster Analysis Resultssupporting
confidence: 91%
“…One soybean mutant (1 % EMS and 8 hours incubation) was not included in the clustering analysis because the seeds cannot grow caused by the toxicity of EMS. This condition was in accordance with the result of Li et al (2017) that a high concentration of EMS showed reduced emergence and physiological damage, including inhibition of the main stem even failed to grow. The dendrogram of genetic relationship resulted in 2 major groups (Figure 3).…”
Section: Cluster Analysis Resultssupporting
confidence: 91%
“…The first soybean TILLING platform was established in 2008, in which four independent mutagenized populations were produced with a range of mutation densities from~1/140 kb to~1/550 kb using both EMS and N-nitroso-N-methylurea (NMU) [30]. Since then, multiple soybean mutant libraries were developed for trait improvement and functional gene analyses [31][32][33][34]. However, in most cases, raw data from seed composition traits including protein, oil, fatty acids, and carbohydrates were not available to perform the correlation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The seeds of soybean ( Glycine max ) cultivars Zhongpin 661(Zp661, ZDD23893), Jidou 12 (JD12, ZDD23040), and Zhonghuang 13 (Zh13, ZDD23876), together with eight other soybean accessions for the allelic variations tests in GmDW1 (Table 8 ), were obtained from the National Crop Gene Bank, Chinese Academy of Agricultural Sciences. The dw dwarf mutant was isolated from an EMS-mutagenized M3 line in the genetic background of Zp661, which was derived from a cross between the soybean cultivar Williams (PI 548631) and Buffalo (PI 424131) (Li et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, d53 is a rice SL-insensitive mutant and the reduced height does not respond to exogenous SL treatment due to a gain-of-function mutation in the D53 protein, acting as a repressor of SL signaling (Zhou et al 2013 ). In soybean, increasing numbers of mutants causing dwarfing have been also identified; these mutants occur following ionizing (gamma rays and fast neutrons) radiation (Zhang et al 2014 ; Hwang et al 2015 ; Cheng et al 2016 ) and/or chemical mutagenesis-generated populations (Li et al 2017 ). However, except for the peroxidase-encoding gene underlying the del3 - 15 locus on chromosome 15 (Hwang et al 2015 ), few dwarf genes have been cloned and characterized to date.…”
Section: Introductionmentioning
confidence: 99%